Prevalence and risk factors for bacterial vaginosis in sexually active females in age group 20-45 years and comparison of Amsel’s criteria with Nugent’s score - Ghattargi, Sharadini; N., Sheela; Dias, Mary (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In recent years Bacterial vaginosis has emerged as a global issue of concern due to its association with cervicitis, salphingitis, endometritis, postoperative infections, Urinary tract infections, pelvic inflammatory infections, spontaneous abortions, preterm delivery, abnormal Pap smears and increased susceptibility to HIV. Bacterial vaginosis is one of the most common lower genital tract infections among women of childbearing age and yet its diagnosis can be problematic. Gardnerella has been reported in upto 50% of women with no signs or symptoms of Bacterial vaginosis. So, it is important to know the prevalence and risk factors of Bacterial vaginosis, so that requirement of screening, early diagnosis and management can be planned. Methods: After obtaining ethical committee approval, hundred consenting patients between 20-45 yrs of women, diagnosis by Amsel’s criteria was done in gynaecology outpatient department and diagnosis by Nugent criteria was done in microbiology laboratory. Results: In present study authors had a prevalence of 37% and among them 48.65% were asymptomatic. Bacterial vaginosis was statistically significantly associated with multipara and the trend was more towards low socio-economic group and lower education. In our study we considered Nugent’s criteria as gold standard and found that Amsel’s criteria had positive predictive value = 88.88%, negative predictive value = 79.67%, sensitivity = 71.11% and specificity = 92.73%. Conclusions: Prevalence of bacterial vaginosis was 37%, which is a significant proportion and therefore screening for bacterial vaginosis may be useful to detect and treat the cases, larger trials are required before any recommendation can be made.